Contextualized idealism: Mohammed Abusalih Mohammed Mansoor’s quest for Islamic reform in contemporary Sri Lanka - Mohamed Zacky, Mohamed Fouz; Careem, Arafath; Ilyas, Inaz (Islamic Research Institute, International Islamic University, Islamabad, 2025)
Mohammed Abusalih Mohammed Mansoor, commonly known as “Ustādh Mansoor”or “MAM Mansoor”by his followers and the general public, has emerged as a prominent advocate for Islamic reform in Sri Lanka over the last threedecades. As a dedicated scholar of the modern evolution of Islam, Mansoorisa key figure within the reformist Islamic intellectual circles in the country. His ideas reflect the complexities and dynamics of Islamic reform within Sri Lanka’s religious landscape, which has often been overlooked compared to the broader context of Islam in the subcontinent. Relying on primary and secondary sources and employing thematic content analysis, this paper aims to address this oversight by exploring Mansoor’s reformist discourses and their implications for shaping the concept of contextualized idealism. Mansoordefines this concept as the process of adapting global developments in Islamic thought to local contexts. The paper arguesthat while Mansoor’s reformist ideas may not significantly contribute to the global discourse on Islamic reform in terms of originality, his uniqueness lies in his ability to relate global ideas to the local sociopolitical realities of the country.Finally, it concludesthat Mansoor’sproject has effectivelypositioned him as an alternative religious authority, challenging traditional theological and legal institutions in the country.